The effects of foam rolling on maximal sprint performance and range of motion - Miller, K. L.; Costa, P. B.; Coburn, J. W.; Brown, L. E. (Journal of Australian Strength and Conditioning, 2019)
Leg foam rolling has been shown to have positive effects on lower body range of motion, showing 3-6% increases in dorsiflexion, knee flexion, and hip flexion with a 15-minute protocol, while maintaining maximum sprint speeds.